Development of a synbiotic low-calorie beverage made from soy and yacon extracts - Manzoni, Marla Simone Jovenasso; Cavallini, Daniela Cardoso Umbelino; Pauly-Silveira, Nadiége Dourado; Roselino, Mariana Nougalli; Rossi, Elizeu Antonio [UNESP] (My University, 2012)
The objective of this study was to develop a new low-calorie symbiotic beverage made from yacon (prebiotic source) and soy extracts, containing probiotic Bifidobacterium animalis ssp. lactis BB-12. The synbiotic beverage was first produced with a range of sucrose concentrations in order to determine ideal sweetness by an acceptance test using a “just-about-right scale”. Sucrose was then replaced by sucralose or aspartame to produce sugar-free beverages. Characteristics including viable cell numbers, physicochemical properties, sensorial characteristics and fructooligosaccharides content were investigated. The ideal sweetness of the beverages with sucrose, aspartame and sucralose were 7.28%, 0.0486% and 0.0167%, respectively. Sucralose exhibited higher scores in acceptance test and was used to replace sucrose in the low-calorie symbiotic beverage. The synbiotic beverage exhibited counts of Bifidobacterium spp. of 108 CFU·mL-1 , sufficient condition to be considered probiotic. The chemical composition of the product was (g/100 g): 2.91 of protein, 1.41 of fat, 2.41 of total carbohydrate; 0.82 of FOS and 148.22 Kj of energy value. The synbiotic beverage developed in this study may be successful in health applications, due to their functional ingredients (soy, probiotic bacteria and yacon prebiotics) that can afford benefits to health or can present disease-preventing properties, beyond their inherent nutritional value. In addition this low-calorie beverage can be consumed by diabetic individuals and people concerned about the ingestion of calories.
Keywords: Fructooligosaccharides; Physicochemical properties; Prebiotics; Probiotic strain; Sensory properties